Kształtowanie się regionów przemysłowych Francji - Sławomir Dorocki (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego, 2008)
The subject of the article is the process of creating industrial regions of France. On the basis of statistical data and referring to the number of employees in the industry, the number of industrial plants and the dimension of industrial production, an attempt at industrial regions delimitation has been made. Workshops dominated industrial activity up to the 19th century. They were mostly situated in densely populated northern parts of France.The factor which initiated the process of industry concentration was the invention of the steam engine. This dependence of industry on the steam engine and coal caused industry concentration in the regions which were rich in natural resources and trained manpower. In the second phase of industry concentration water-energy basis played the main role. It led to the creation of large industrial centres in the mountains and around big cities. Due to the industrial growth index the industrial centres of France were situated in four regions. The most industrialized region was the North, covering Flandres, Picardy, Île-de-France and Upper Normandy – the Seine Valley. The eastern region covered Ardenne, Champagne, Lorraine and Alsace. The third region was Lyon and St-Étienne and the regions of the Alps and the Saone Valley. In the south the regions of Provence with Marseille and the Rhone estuary were standing ou